Greener and Scalable E-fuels for Decarbonization of Transport - Agarwal, Avinash Kumar; Valera, Hardikk; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book highlights ways of using gaseous and liquid e-fuels like hydrogen (Hb2(B), methane (CHb4(B), methanol (CHb3(BOH), DME (CHb3(B-O-CHb3(B), Ammonia (NHb3(B), synthetic petrol and diesel, etc in existing engines and their effects on tailpipe emissions. The contents also cover calibration and optimization procedure for adaptation of these fuels. the volume also discusses the economical aspect of these fuels. Chapters include recent results and are focused on current trends of automotive sector. This book will be of interest to those in academia and industry involved in fuels, IC engines, engine instrumentation, and environmental research.s
Introduction of Greener and Scalable E-fuels for Decarbonization of Transport -- Potential of E-Fuels for Decarbonization of Transport Sector -- A Historical Perspective on the Biofuel Policies in India -- Hydrogen as Maritime Transportation Fuel: A Pathway for Decarbonization -- Improving Cold Flow Properties of Biodiesel, and Hydrogen-biodiesel Dual-fuel Engine Aiming Near-zero Emissions -- Assessment of Hydrogen as an alternative fuel: Status, prospects, performance and emission characteristics -- Effectiveness of hydrogen and nanoparticles addition in eucalyptus biofuel for improving the performance and reduction of emission in CI engine -- The Roles of Hydrogen and Natural Gas as Biofuel Fuel-Additives towards Attaining Low Carbon Fuel-Systems and High Performing ICEs.
Keywords: Engines; Engine Technology; Biomass energy; Fuel switching; Synthetic fuels